Systematic Literature Review: Model Pembelajaran RADEC terhadap Keterampilan Berpikir Siswa: Systematic Literature Review - Andriyani, Fitria; Ekawati, Ratna; Sukoriyanto (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
The RADEC learning model is an alternative learning model that can be used by educators in current teaching, in line with the demands of HOTS learning. However, this learning model has not yet been widely implemented in elementary schools, in particular. This learning model has several learning characteristics that align with the demands of 21st-century education, such as being able to motivate and actively involve students in the learning process, training students to learn independently, being able to contextualize a student's understanding of the material in relation to real life, being student-centered, and providing opportunities for students to understand and delve into the subject matter. Therefore, the application of the RADEC learning model can help an educator to facilitate the delivery of the material. This study aims to determine the effect of the RADEC learning model on students' critical thinking skills. This research uses a systematic literature review with 4 stages, namely the identification stage, selection stage, verification stage, and combination stage, followed by conclusion. The results of this study were obtained from the analysis of 10 articles relevant to the RADEC learning model published in the last 5 years. Based on the analysis of these 10 articles, it was concluded that the RADEC learning model has a positive effect on students' critical thinking skills.